Pengembangan Bahan Ajar Matematika Berbasis Ekonomi Syariah Untuk Madrasah Tsanawiyah - Mulin Nu’man (Jurnal Fourier, 2015)
This research aims to develop mathematical teaching materials based on sharia economy for madrasah tsanawiyah students with good quality. The method used in the study is the development model adapted from Borg & Gall is the preliminary stage, development, and validation. The preliminary stage includes literature studies, analysis of the needs and characteristics of students, and to plan and choose the design of teaching materials. The development phase includes determining the competence standard, basic competence, indicators, and the subject matter, compiling teaching materials math, and prepare research instruments. The validation phase includes validation expert and revisions. Results of the study are social arithmetic teaching materials based on sharia economy. Each material begins with the problem of economic comparison of Islamic and conventional. The feasibility of the value of teaching materials is Very Good for aspects of the look and Very Good for the material aspects. With these criteria very well, teaching materials are feasible for use in the learning of mathematics in the social arithmetic material.